The Role of Tumor-Associated Myeloid Cells in Modulating Cancer Therapy - Neophytou, Christiana M.; Pierides, Chryso; Christodoulou, Maria-Ioanna; Costeas, Paul; Kyriakou, Theodora-Christina; Papageorgis, Panagiotis (Frontiers in Oncology, 2020)
Myeloid cells include various cellular subtypes that are distinguished into mononuclear and polymorphonuclear cells, derived from either common myeloid progenitor cells (CMPs) or myeloid stem cells. They play pivotal roles in innate immunity since, following invasion by pathogens, myeloid cells are recruited and initiate phagocytosis and secretion of inflammatory cytokines into local tissues. Moreover, mounting evidence suggests that myeloid cells may also regulate cancer development by infiltrating the tumor to directly interact with cancer cells or by affecting the tumor microenvironment. Importantly, mononuclear phagocytes, including macrophages and dendritic cells (DCs), can have either a positive or negative impact on the efficacy of chemotherapy, radiotherapy as well as targeted anti-cancer therapies. Tumor-associated macrophages (TAMs), profusely found in the tumor stroma, can promote resistance to chemotherapeutic drugs, such as Taxol and Paclitaxel, whereas the suppression of TAMs can lead to an improved radiotherapy outcome. On the contrary, the presence of TAMs may be beneficial for targeted therapies as they can facilitate the accumulation of large quantities of nanoparticles carrying therapeutic compounds. Tumor infiltrating DCs, however, are generally thought to enhance cytotoxic therapies, including those using anthracyclines. This review focuses on the role of tumor-infiltrating and stroma myeloid cells in modulating tumor responses to various treatments. We herein report the impact of myeloid cells in a number of therapeutic approaches across a wide range of malignancies, as well as the efforts toward the elimination of myeloid cells or the exploitation of their presence for the enhancement of therapeutic efficacy against cancer.